Self-medication in nursing students in a Private University in San Juan de Lurigancho, 2017 - Felipe Medez, Deysy (2017)
Objective: To determine self-medication in nursing students in a Private University in San Juan de Lurigancho, 2017. Materials and Methods: It was decided to conduct a descriptive, observational, crosssectional observational study. A structured questionnaire was designed and facilitated with 11 items, collecting information from the variable, and a survey was conducted on 84 students in a Private University. Results: According to the demographic factor, 100% of the respondents used self-medication, the highest percentage was female with 84.5% and the age group between 18 and 25 years old with 64.3%, 78.6% are single individuals. Regarding the economic factor, according to students who perform some job, there is a tendency to self-medication in 59.5%, 31% of students receives an acceptable monthly salary and 54.8% are incorporated into a social health security program. In terms of the social factor, students tend to go to the pharmaceutical establishment in 57% after health problems affect them, 42.9% of students take into account the suggestion of the care staff, 83.3% buy medicine there. 56% of individuals acquired drugs that were showed by television advertising. Conclusion: Self-medication is a common practice and it includes demographic, economic and social factors.